An electrochemical alternative for evaluating the antioxidant capacity in walnut kernel extracts. (1st November 2022) - Ruiz-Caro, Pablo; Espada-Bellido, Estrella; García-Guzmán, Juan José; Bellido-Milla, Dolores; Vázquez-González, Marcos; Cubillana-Aguilera, Laura; Palacios-Santander, José María
Graphical abstract: Highlights: An alternative methodology for antioxidant activity evaluation in walnut kernels. Fast ultrasonic methods for defatting walnuts and ethanolic extraction of polyphenols. A simple, precise and inexpensive electrochemical index approach is proposed. A high correlation between ABTS assay and electrochemical index approach was found. Abstract: A fast, precise and inexpensive alternative for evaluating the antioxidant activity (AA) in walnut kernel extracts is proposed. Traditional ABTS assay and an electrochemical index approach have been applied to evaluate the AA in walnuts. A fast and efficient defatting of the walnuts by ultrasound assisted extraction (UAE) was carried out. Later, for the extraction of polyphenolic compounds, a procedure based on UAE in ethanolic medium was used. The AA of the sample ethanolic extracts was expressed as both % of inhibition by the ABTS spectrophotometric method and the electrochemical index approach (EI) obtained by the ratio between current and potential peak values using differential pulse voltammetry (DPV) at a Sonogel-Carbon electrode. The behaviour of the EI approach have been explored using six polyphenols standards and walnut kernel extracts at pH 2. All the polyphenols appeared at an oxidation potential between 0.476 and 0.778 V. Eleven samples available to consumers were analysed. A high significant correlation (R 2 = 0.927) between the spectrophotometric measurements and the EI approach of the walnut extracts was obtained.